A study of damar minyak and seraya as material for gambus Johor soundboard / Abdullah Mohd Redza - Abdullah, Mohd Redza (2017)
Wood is the best material for chordophones instrument’s soundboard, and among all wood species, European Spruce is of the highest quality in terms of acoustical properties according to western scholars and most musical instrument makers. Although spruce does not exist in Malaysia, there are several softwoods in Malaysia having physical and mechanical properties that are similar to the European spruce and one of them is the damar minyak. In addition to this, according to local gambus makers, seraya has been identified as one of the best and most preferable wood (material) for soundboard. Therefore, damar minyak and seraya have been selected as study material in the production of the gambus Johor soundboard. The primary purpose of this study is to apply a scientific approach in identifying the acoustical properties of damar minyak and seraya according to its physical and mechanical properties. The approach was focused on the speed of sound through wood, characteristic impedance and sound radiation coefficient. The data complied from these elements were used to compute the acoustic formula which objectively aims to identify the potential of wood without using the trial and error method. Then, two gambus instruments were constructed with selected damar minyak and seraya for each soundboard. The gambus production process was also documented to serve as future reference and guideline in the production of gambus. Finally, the two gambus were played (demonstrated) and questionnaires were distributed to the ethnomusicologist, gambus makers, gambus players and gambus students in order to analyse and prove the acoustical quality and sound characteristic of damar minyak and seraya as gambus Johor’s soundboards.